2013
DOI: 10.1080/13548506.2013.774431
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the post-delivery perceived stress inventory

Abstract: This article presents the post-delivery perceived stress inventory (PDPSI) and its psychometric properties. This inventory is unique in that it links the measurement of perceived stress to events experienced during and after delivery. A total of 235 French-speaking, primiparous mothers completed the PDPSI two days after their delivery. To evaluate the predictive validity of the PDPSI on anxiety and depression, participants also completed the EPDS and the STAI two days and six weeks postpartum. The exploratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
0
15
0
2
Order By: Relevance
“…We used the cut-off of a score of 17 or higher for probable depression [55,56]. Maternal stress levels were measured using the Perceived Stress Scale (PSS) (range: 0-40) [57].…”
Section: Data Collectionmentioning
confidence: 99%
“…We used the cut-off of a score of 17 or higher for probable depression [55,56]. Maternal stress levels were measured using the Perceived Stress Scale (PSS) (range: 0-40) [57].…”
Section: Data Collectionmentioning
confidence: 99%
“…[5] Stress can, however, have substantial repercussions for women's psychological health, such as their anxiety or risk of depression, particularly in the early postpartum period. [2,[21][22][23] It is therefore important to boost mothers' resources to deal with and decrease this stress. However, despite the fact that intervention in the early postnatal period has been documented as highly relevant, few studies have addressed this issue.…”
Section: Stressmentioning
confidence: 99%
“…However, research has shown that mothers' stress during this postpartum period is not dependent on specific variables, and can be experienced by all mothers, regardless of, for example, birth method or age. [2] 4.2 Effect of the interview on staff satisfaction…”
Section: Use Of the Interviewmentioning
confidence: 99%
See 2 more Smart Citations